IDENTIFIKASI KARAKTER MORFOLOGI DAN ANATOMI TANAMAN MANGGA (mangifera) Di KECAMATAN BUNGKU TENGAH KABUPATEN MOROWALI - Iban, Iban; Adelina, Enny; Sahiri, Nirwan (AGROTEKBIS, 2017)
The objective of this study was to determine the characteristics ofmangoplant based on specific characteristic of morphology and anatomy of mango plant leaves in the village of Ipi and Bahomohoni, Subdistrict of Central Bungku, Morowali District. Observation of morphological features has done in the village of Ipi and Bahomohoni, while the anatomical observations done in the Laboratory of Biotechnology, Faculty of Mathematics and Natural Sciences, TadulakoUniversity, from June until August 2016. The observed morphological parameters include plant age, height plant, stem diameter, canopy diameter, canopy shape andbars color. Variables of leaf anatomy consists of stomata size, size of the epidermis, stomatal density and stomatal index. The result showed that the morphological and anatomical characters observed based on a cluster analysis described dendogram form. The results of cluster analysis of both villages onthe distance of 0.7 resulted five accession namelyBI14, IP13, IP1, IP9 and BI1. Highest stomatal index of the both villages is accession IP7 and the lowest accession is BI14, while accessions has the highest stomata density/mm2is accession IP13, and the lowest one is accession IP9. That is as initial step to find the source ofhigh quality mango seed.Keywords: Anatomy, Mango, morphology.